Synthesis of furan-based molecule for organic electronics - Kwong, Justin (Nanyang Technological University, 2023)
Organic electronics are getting increasingly popular as it could be a sustainable and renewable alternative to traditional silicon electronics. Currently, organic electronics applications make use of thiophene, which are derived from petroleum. Furans, which are derived from biomass, boasts similar or even greater performance than thiophene in organic electronic applications and could be a suitable and sustainable alternative to thiophene and its derivations This project focuses on the chemical synthesis and characterization of various furan-based compounds, leading up to the desired novel molecule, compound JK9. Various synthesis methodologies like Suzuki Coupling, Friedel-Crafts acylation and esterification were employed to attempt to synthesize the desired compound JK9: 2,7-dibromo-4,4,9,9-tetrahexadecyl-4,9-dihydro-s-indaceno [1,2-b:5,6-b'] difuran. This report discusses the various furan-based compounds successfully synthesized up until JK7, which is an intermediate in the proposed synthesis to obtain compound JK9. All compounds synthesized in this project were characterized by FTIR and NMR spectroscopy. However, compound JK6 was characterized by FTIR and mass spectroscopy due to solubility issues.